Perlindungan Hukum Terhadap Konsumen Pelanggan Air Minum Isi Ulang - Rahdiansyah, Rahdiansyah (UIR Law Review, 2018)
Community needs for clean, healthy and hygienic water from time to time increasing, as the number of consumers increases, the number of water depots minumpun more and more. Moreover, the price offered by refill drinking water is also cheaper compared to bottled drinking water, so the drinking water depots are located on the side of the road much in demand by consumers for more economical and economical reasons. Establishment of Refill Depots shall be processed in accordance with applicable laws and regulations, ranging from business permit, sign of company list, business permit, healthy recomendation recommendation, and examination / test of water samples. Supervision of the stands The drinking water refill depots must be through the supervision of the Municipal Health Service, by conducting field observations, sanitary inspections, sampling of drinking water for inspection. Disperindagtamben, conducting technical permit engineering, technical machinery / equipment, business legality, registration. Hall of POM, supervise if the water consumed causes illness and even poisoning, and POM Hall as a designated and accredited laboratory.Provisions Legislation that regulates the protection of consumer law should be able to provide legal certainty to users of water refills so that consumers are protected, both health and services / services provided by the owner of water refill Depot.